E-learning and development: Lessons from multi-disciplinary capacity strengthening - Babu, Suresh Chandra (Commonwealth of Learning, 2014)
This paper documents the experience and lessons from implementing an e-learning program aimed at creating multidisciplinary research capacity. It presents a case study of bringing together a multidisciplinary group of professionals on-line to learn the skills needed to be a successful researcher in the context of HIV/AIDS and food security problems in Eastern and Southern Africa. Lessons from the experience for future development of similar courses indicate that some of the factors that can enhance the success of e-learning programs in developing countries are: assessing the needs of the participants, easy access to educational technology, addressing the differing learning styles of the participants, continuous interaction and commitment of course moderators, enabling access to open access learning materials and combining various pedagogical approaches. The paper concludes that enhancing the skills of professionals in developing countries through e-learning programs is imperative to meet the human capacity needs for greater economic development and service delivery.